The Development of Good Micro, Small and Medium Enterprises Governance Indicators - Dito Rinaldo; Puteri Andika Sari; Wiendy Puspita Sari; Rediawan Miharja (Faculty of Economic and Business, 2023)
A systematic literature review method was used in this study to find good governance for micro, small, and medium-sized businesses (MSMEs). The SEM-PLS approach was utilized to assess the effect of MSMEs' owners' competencies on the level of governance model implementation and the performance of MSMEs. The test results suggest implementing the governance model's concept can improve business performance. To be effective, however, owners of MSMEs must be willing to invest in their professional growth. Thus, based on the research findings, the MSMEs governance model, which is unique to this study, can serve as a standard for MSMEs' performance and a reference for various stakeholders involved in MSMEs' development initiatives.JEL Classification: G3, M21How to Cite:Rinaldo, D., Sari, P. A., Sari, W. P. & Miharja, R. (2023). The Development of Good Micro, Small and Medium Enterprises Governance Indicators. Etikonomi, 22(1), 93–118. https://doi.org/10.15408/etk.v22i1.25625.